Malnutrition Risk Screening In HIV/AIDS Patients Using Modified SGA-HIV: Scoping Review - Irman, Irman; Hanim, Risyda Zakiyah (Universitas Pendidikan Indonesia, 2024)
Introduction: Human immunodeficiency virus (HIV) is a condition that targets the immune system. Individuals with HIV are at risk of malnutrition when their CD4 counts drop below 200. Purpose: This study seeks to explore the efficacy of Modified SGA-HIV in assessing the risk of malnutrition in HIV/AIDS patients. Methods: A comprehensive search was conducted across multiple databases, including ScienceDirect (346), EBSCO-host (47), ClinicalKey Nursing (11), PubMed (98), and Google Scholar (284) covering the period from 2018 to 2024. The Joanna Briggs Institute (JBI) Critical Appraisal was used to assess and analyze the methodological quality of the articles. Findings: The initial database search using PRISMA Literature Review yielded 786 articles, which were refined to exclude duplicates (665), screen for relevance based on title/abstract (98), and finally assess the eligibility of full-text articles (n = 27), resulting in the identification of four (4) relevant articles. Conclusion: The analysis of these four articles supports the effectiveness of Modified SGA-HIV in screening for malnutrition risk in HIV/AIDS patients.